Application of ultrasonication as pre-treatment for freeze drying: An innovative approach for the retention of nutraceutical quality in foods. (15th March 2023) - Waghmare, Roji; Kumar, Manoj; Yadav, Rahul; Mhatre, Priyank; Sonawane, Sachin; Sharma, Swati; Gat, Yogesh; Chandran, Deepak; Radha,; Hasan, Muzaffar; Dey, Abhijit; Sarkar, Tanmay; et al.
Graphical abstract: Highlights: The influence of the ultrasonic assisted freeze drying (US + FD) is reviewed. Thermally sensitive compounds and physic-chemical properties retained in the final dried product. US pre-treatment improves the drying rate during FD. US is a potential pretreatment to reduce drying time and energy consumption. Abstract: Freeze drying (FD) is an important and highly effective technology in food industry for retaining the quality in final dried product. This drying technique is performed at lower temperatures, restricting the damage suffered by thermally sensitive ingredients. However, FD consumes large amount of energy and required more time than conventional drying methods. The utilization of ultrasonic technology (US) as pre-treatment before FD represents a promising alternative in accelerating the drying process, decreases energy consumption and maintaining quality as compared to the non pre-treated sample. This review summarizes research progress and current studies in ultrasonic as pre-treatment for freeze drying (US + FD) technique. The impact of US + FD on phytochemical, color, texture and micro-structure of food are well summarized. The review also suggests that the optimised US treatment parameters are required to improve heat and mass transfer in food samples which help in speed up the drying process and reduction of drying time.